Ancient Indian epistemology and modern cognitive science: Exploring vedic insights in contemporary thought processes - Thuong, Nguyen Le Thy; Untara, I Made Gami Sandi (Dharmakirti : International Journal of Religion, Mind and Science, 2024)
Background: This article explores the connections between the concept of anviksiki in Hindu philosophy and theories in cognitive science, and how these principles can be applied in modern education. Anviksiki, which focuses on critical thinking and deep reflection, is considered to have strong relevance to cognitive science concepts such as information processing, perception, and decision-making. Methods: The method used in this research is literature study and comparative analysis, by reviewing various literatures that discuss Hindu philosophy and cognitive science in depth. The analysis shows that anviksiki can provide an additional perspective in understanding how humans think and process information, especially in the context of moral and ethical reflection. Finding: In education, the principle of anviksiki that emphasises self-reflection and critical thinking can enrich students' learning process. This concept supports active learning methods that allow students to construct their own understanding, in a way that is in line with Piaget's theory of constructivism. In addition, cognitive science provides practical insights into information processing and memory, which can be used to design more effective teaching strategies. Conclusion: The conclusion of this study confirms that anviksiki can be integrated with cognitive science to create a holistic approach to education, which enriches intellectual, ethical and reflective aspects. By combining Hindu wisdom and cognitive science insights, education can support the development of balanced individuals, who are able to think critically and understand the moral consequences of their decisions. This research reveals that Anviksiki, as a philosophy of critical thinking in the Hindu tradition, has strong relevance to concepts in modern cognitive science, particularly in analytic approaches, logic, and deductive methods. Thus, the heritage of Hindu thought not only demonstrates traditional wisdom but also presents a philosophical foundation that supports contemporary cognitive exploration. Novelty/Originality of this article: This research offers a new perspective by bridging the ancient philosophy of Anviksiki with modern cognitive science, demonstrating the continuity of concepts in the critical thinking process involving logical analysis and deductive methods. It provides new insights in understanding the contribution of the Hindu tradition of thought to the development of cognitive theory today.